Cost analysis of minimally invasive compared to conventional mitral valve surgery. Issue 5 (1st October 2016) - Verbrugghe, Peter; De Praetere, Herbert; Meuris, Bart; Rega, Filip; Meyns, Bart; Goodall, Gordon; Herijgers, Paul
Abstract : Objective Minimally invasive cardiac surgery through port-access has been advocated as a valid alternative for conventional full sternotomy approaches. However, the full economic consequences are unclear. We undertook an analysis of our own data to address these uncertainties. Methods Retrospective data, on patients who underwent single mitral valve surgery (repair or replacement) were included in our analysis. These were allocated into two cohorts based upon the intended surgical approach: either port-access or full sternotomy. Propensity score matching was performed to avoid confounding factors. Comprehensive clinical and cost data, based on hospital charges and a cost allocation model, were collected. Results There were fewer complications with port-access versus full sternotomy. Operation times were longer but there was a shorter intensive care and total hospital stay. Port-access resulted in comparable overall costs (€ 21, 041 ± 3, 743 compared with € 23, 999 ± 15, 007 for full sternotomy; mean and standard deviation). A breakdown into accounting groups showed reductions in several costs categories (i.e. nursing costs, technical fees, and pharmacy drugs/implants) except for materials. Patient costs were higher for the port-access group due to higher material costs (€ 1, 917 ± 602 versus € 1, 145 ± 659; mean and standard deviation). From a hospital perspective direct costs were comparable in both cohorts. Conclusion Port-access mitral valve surgery in UZ Leuven has at least comparable short-term clinical results as full sternotomy. It is associated with comparable costs for the acute-treatment phase for the health insurance system and the hospital, but higher patient costs.